(untitled) (Edad Media. Revista de Historia, 2025)
This paper aims to explain how the nobility was formed in the Kingdom of Valencia over the course of the 14th century. It focuses on the establishment of legal foundations that distinguished the aristocracy from other social groups or strata. Furthermore, it explores how this process gave rise to a distinct identity for the Valencian nobility as a differentiated social order, marked by its own names, symbols, discourses, and a unique self-image in which chivalric ideology played a central role.